A polyvinyl chloride high impact modifier and preparation method thereof

High impact modifiers were prepared by using modified cyclodextrin and specially treated methyl methacrylate-ethyl acrylate copolymer, which solved the problem of degradation in existing impact modifiers in low temperature environments. , high impact resistance and elongation at room temperature and low temperature are achieved, and impact resistance is maintained after sudden heat in low temperatures.

CN118955956BActive Publication Date: 2025-01-03SHANDONG YUANBANG NEW MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411453371.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-03
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing impact modifiers have poor impact resistance in low-temperature environments, and the impact resistance of the room temperature decreases after a sudden heat in low temperature, making the initial performance unable to be restored.

Method used

Modified cyclodextrin is used as the core of the impact modifier and with the specially treated methyl methacrylate-ethyl acrylate copolymer as the shell, a high impact modifier is prepared by controlling the stirring temperature and time. Improve the impact resistance of the material at room temperature and low temperature, and maintain the impact resistance after sudden heat in low temperatures.

Benefits of technology

It significantly improves the impact strength and elongation of breaking polyvinyl chloride materials, maintains high transparency and low haze, and maintains high impact resistance and elongation in low temperature environments, and after a sudden heat in low temperatures It can still maintain a high impact strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a polyvinyl chloride high impact modifier and a preparation method thereof, and belongs to the field of polymer compound compositions. The raw materials of the polyvinyl chloride high impact modifier include a modified cyclodextrin core and a shell material, and the mass ratio of the two is 6.5-7.5:4. The impact modifier of the invention can effectively improve the impact resistance of polyvinyl chloride materials at low temperatures. According to the method in GB / T1043.1-2008, the impact strength of the sample at 0°C, -20°C, and -40°C is tested, and the impact strength at 0°C is 45.5-46.3KJ / m 2 The impact strength at ‑20°C is 39.8‑41.3KJ / m 2 The impact strength at ‑40°C is 33.6‑35.5KJ / m 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyvinyl chloride high-impact modifier and a preparation method thereof, belonging to the field of polymer compound compositions. Background Art

[0002] Polyvinyl chloride (PVC) hard products have the characteristics of high strength, high hardness, flame retardancy, corrosion resistance, insulation, etc., and are widely used in various industries due to their good physical and chemical properties and low prices. However, the notched impact strength of a single hard PVC product is very low, the toughness is poor, and it is very easy to crack when impacted. Therefore, in the processing formula, impact modifiers need to be added to obtain sufficient impact performance to achieve the purpose of toughening and strengthening.

[0003] At present, the impact performance of PVC hard products is almost entirely improved by the method of blending and toughening, that is, adding various types of modifiers to PVC resin to improve the toughness of the product. This method is a kind of physical modification, which will lead to poor resin dispersion, poor adjuvant absorption, uneven plasticization, low toughening efficiency, etc. Therefore, it is very necessary to study and produce a special high impact modifier for PVC with high hardness and high toughness.

[0004] Chlorinated polyethylene (CPE) is a rubber elastomer network polymer. Its modification mechanism is to form a network in the PVC material. It is evenly distributed in the PVC resin by the mixing action of the processing machinery, which can reduce the processing melt viscosity of PVC. When PVC and CPE are blended, as the amount of CPE increases, the impact strength of the profile also increases accordingly, but the tensile strength decreases to a certain extent.

[0005] ACR impact modifiers are "core-shell" copolymers, which consist of two parts. The core is a low-crosslinked acrylic rubber polymer that can be evenly dispersed in the PVC substrate and can interact with the PVC substrate. ACR impact modifiers have small elastic deformation under the action of heat, which is manifested as a low rate of dimensional change of profiles after heating. When performing proportioning processing, ACR impact modifiers show a wide processing range, and the surface finish of the profiles is significantly improved compared to the CPE system.

[0006] Regardless of the type of impact modifier, it is often limited to improving the impact resistance in a room temperature environment. In actual applications, it is found that due to the performance limitations of the impact modifier itself, the low-temperature performance of the material will be poor. First, the elongation of the material at low temperatures decreases, which in turn leads to a more serious decrease in impact resistance at low temperatures. Moreover, after sudden heating in a low-temperature environment, the impact resistance at room temperature will also decrease.

[0007] In summary, although the impact modifiers in the prior art can improve the impact resistance of materials, they are limited to impact resistance at room temperature. When the material is in a low-temperature environment, the elongation will decrease, and the impact resistance will also decrease to a large extent. In addition, after sudden heating in a low-temperature environment, the impact resistance at room temperature will also decrease, and the initial impact resistance cannot be restored. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the defects of the prior art, use cyclodextrin as the core of the impact modifier, and perform special treatment on it, and then use the specially treated methyl methacrylate-ethyl acrylate copolymer as the shell to finally prepare the impact modifier, which can not only improve the impact resistance of the material at room temperature, but also improve the impact resistance of the material at low temperature, and after sudden heating in a low temperature environment, it can also better maintain the impact resistance of the material at room temperature and maintain a large elongation.

[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0010] A polyvinyl chloride high impact modifier, characterized in that the raw materials of the polyvinyl chloride high impact modifier include a modified cyclodextrin inner core and an outer shell material, and the mass ratio of the two is 6.5-7.5:4.

[0011] The following are further improvements to the above technical solution:

[0012] The preparation method of the modified cyclodextrin inner core is as follows: 2-amino-β-cyclodextrin is mixed with deionized water, stirred to completely dissolve, and a cyclodextrin aqueous solution is obtained, and then sodium polyphosphate is added to the cyclodextrin aqueous solution, and an ice-water bath is used to control the stirring temperature to 1-3°C, and stirring is performed for 170-190 minutes. After the stirring is completed, the pH is adjusted to 5.1-5.3, and then disuccinimidyl glutarate is added, and the ice-water bath is continued to be used to control the stirring temperature to 1-3°C, and stirring is performed for 14.5-15.5 hours. After the stirring is completed, the product is dialyzed in deionized water and dried to obtain a modified cyclodextrin inner core;

[0013] The mass ratio of the 2-amino-β-cyclodextrin, deionized water, sodium polyphosphate, and disuccinimidyl glutarate is 45-55:450-550:0.9-1.1:32-37;

[0014] The preparation method of the shell material comprises the following steps: mixing methyl methacrylate-ethyl acrylate copolymer with toluene, stirring for 13-17 minutes, adding polyaspartic acid ester after the stirring is completed, and continuing to stir for 13-17 minutes, adding sodium methoxide after the stirring is completed, controlling the temperature to 115-135° C., stirring for 7.5-8.5 hours, and removing toluene by decompression after the stirring is completed to obtain the shell material;

[0015] The mass ratio of the methyl methacrylate-ethyl acrylate copolymer, toluene, polyaspartic acid ester and sodium methoxide is 14-16:70-80:6.5-7.5:0.9-1.1.

[0016] In the preparation method of the shell material, in the methyl methacrylate-ethyl acrylate copolymer, the mass ratio of the methyl methacrylate monomer to the ethyl acrylate monomer is 5.5-6.5:4.

[0017] In the preparation method of the shell material, the density of polyaspartic acid is 1.22 g / cm 3 .

[0018] In the preparation method of the shell material, the density of the methyl methacrylate-ethyl acrylate copolymer is 0.915-0.918 g / cm 3 .

[0019] The preparation method of the high impact modifier is as follows: controlling the temperature to 172-178°C, heating the shell material to a molten state, obtaining a shell liquid for standby use, and then placing the modified cyclodextrin core in a fluidized bed, and granulating the modified cyclodextrin core with the shell liquid under a nitrogen atmosphere, and after cooling, obtaining particles, namely the high impact modifier.

[0020] Compared with the prior art, the present invention achieves the following beneficial effects:

[0021] The impact modifier of the present invention can effectively improve the impact resistance of polyvinyl chloride materials. The impact strength is tested according to the method in GB / T1043.1-2008, and the impact strength is 52.7-54.1KJ / m 2 ;

[0022] The impact modifier of the present invention can effectively improve the impact resistance of polyvinyl chloride materials at low temperatures. According to the method in GB / T1043.1-2008, the impact strength of the sample at 0°C, -20°C and -40°C is tested, and the impact strength at 0°C is 45.5-46.3 KJ / m 2 , the impact strength at -20℃ is 39.8-41.3KJ / m 2 , the impact strength at -40℃ is 33.6-35.5KJ / m2 ;

[0023] The impact modifier of the present invention can make the material maintain high impact resistance after being suddenly heated in a low temperature environment. The samples are placed at 0°C, -20°C and -40°C for 4 hours respectively. After the placement, they are immediately placed in an oven with a constant temperature of 80°C for sudden heating. The sudden heating time is 60 minutes. After the sudden heating is completed, the samples are naturally cooled to room temperature and then tested. After the sudden heating at 0°C, the impact strength of the material is 48.1-48.8KJ / m 2 After sudden heating at -20℃, the impact strength of the material is 45.1-45.9KJ / m 2 After sudden heating at -40℃, the impact strength of the material is 41.7-42.6KJ / m 2 ;

[0024] The impact modifier of the present invention can effectively improve the elongation at break of polyvinyl chloride materials, and can make the materials maintain a high elongation at break in a low temperature environment. According to the method in GB / T528-2009, the elongation at break of the sample at room temperature is tested, and the elongation at break of the sample at 0°C, -20°C, and -40°C is tested respectively. The elongation at break at room temperature is 446-453%, the elongation at break at 0°C is 429-435%, the elongation at break at -20°C is 413-422%, and the elongation at break at -40°C is 359-377%;

[0025] The impact modifier of the present invention can make polyvinyl chloride maintain high transparency and low haze. According to the method in GB / T2410-2008, the transparency and haze of the sample are tested, and the transparency is 91.5-92.2%, and the haze is 4.6-5.5%;

[0026] The impact modifier of the present invention can make polyvinyl chloride have higher strength. According to the method in GB / T9341-2008, the bending strength of the sample is tested, and according to the method in GB / T1040.1-2018, the tensile strength of the sample is tested. The bending strength is 90.6-91.5MPa, and the tensile strength is 65.4-66.1MPa. DETAILED DESCRIPTION Example 1

[0027] The raw materials of the polyvinyl chloride high impact modifier include a modified cyclodextrin core and a shell material, and the mass ratio of the two is 7:4;

[0028] The preparation method of the modified cyclodextrin core is:

[0029] Mix 2-amino-β-cyclodextrin with deionized water, stir to completely dissolve it, and obtain a cyclodextrin aqueous solution. Then, add sodium polyphosphate to the cyclodextrin aqueous solution, use an ice-water bath to control the stirring temperature to 2°C, stir for 180 minutes, and after the stirring is completed, adjust the pH to 5.2, and then add disuccinimidyl glutarate, continue to use an ice-water bath to control the stirring temperature to 2°C, stir for 15 hours, and after the stirring is completed, dialyze the product in deionized water and dry it to obtain a modified cyclodextrin core;

[0030] The mass ratio of the 2-amino-β-cyclodextrin, deionized water, sodium polyphosphate and disuccinimidyl glutarate is 50:500:1:35.

[0031] The preparation method of the shell material is:

[0032] Mix methyl methacrylate-ethyl acrylate copolymer with toluene and stir for 15 minutes. After stirring, add polyaspartic acid ester and continue stirring for 15 minutes. After stirring, add sodium methoxide and control the temperature to 125° C. and stir for 8 hours. After stirring, remove toluene by decompression to obtain a shell material.

[0033] The mass ratio of the methyl methacrylate-ethyl acrylate copolymer, toluene, polyaspartic acid ester and sodium methoxide is 15:75:7:1;

[0034] In the methyl methacrylate-ethyl acrylate copolymer, the mass ratio of methyl methacrylate monomer to ethyl acrylate monomer is 6:4;

[0035] The density of the methyl methacrylate-ethyl acrylate copolymer is 0.917 g / cm 3 ;

[0036] The density of the polyaspartic acid is 1.22 g / cm 3 .

[0037] The preparation method of the high impact modifier is:

[0038] The temperature is controlled at 175°C, the shell material is heated to a molten state, and a shell liquid is obtained for use. The modified cyclodextrin core is then placed in a fluidized bed. Under a nitrogen atmosphere, the modified cyclodextrin core is granulated with the shell liquid. After cooling, the granules, i.e., the high impact modifier, are obtained. Example 2

[0039] The raw materials of the polyvinyl chloride high impact modifier include a modified cyclodextrin core and a shell material, and the mass ratio of the two is 6.5:4;

[0040] The preparation method of the modified cyclodextrin core is:

[0041] Mix 2-amino-β-cyclodextrin with deionized water, stir to completely dissolve it, and obtain a cyclodextrin aqueous solution, then add sodium polyphosphate to the cyclodextrin aqueous solution, use an ice water bath to control the stirring temperature to 1°C, stir for 170 minutes, and after the stirring is completed, adjust the pH to 5.1, and then add disuccinimidyl glutarate, continue to use an ice water bath to control the stirring temperature to 1°C, stir for 14.5 hours, and after the stirring is completed, dialyze the product in deionized water and dry it to obtain a modified cyclodextrin core;

[0042] The mass ratio of the 2-amino-β-cyclodextrin, deionized water, sodium polyphosphate and disuccinimidyl glutarate is 45:450:0.9:32.

[0043] The preparation method of the shell material is:

[0044] Mix methyl methacrylate-ethyl acrylate copolymer with toluene and stir for 13 minutes. After stirring, add polyaspartic acid ester and continue stirring for 17 minutes. After stirring, add sodium methoxide and control the temperature to 115° C. and stir for 8.5 hours. After stirring, remove toluene by decompression to obtain a shell material.

[0045] The mass ratio of the methyl methacrylate-ethyl acrylate copolymer, toluene, polyaspartic acid ester, and sodium methoxide is 14:70:6.5:0.9;

[0046] In the methyl methacrylate-ethyl acrylate copolymer, the mass ratio of methyl methacrylate monomer to ethyl acrylate monomer is 5.5:4;

[0047] The density of the methyl methacrylate-ethyl acrylate copolymer is 0.915 g / cm 3 ;

[0048] The density of the polyaspartic acid is 1.22 g / cm 3 .

[0049] The preparation method of the high impact modifier is:

[0050] The temperature is controlled at 172°C, the shell material is heated to a molten state, and a shell liquid is obtained for use. The modified cyclodextrin core is then placed in a fluidized bed. Under a nitrogen atmosphere, the modified cyclodextrin core is granulated with the shell liquid. After cooling, the granules, i.e., the high impact modifier, are obtained. Example 3

[0051] The raw materials of the polyvinyl chloride high impact modifier include a modified cyclodextrin core and a shell material, and the mass ratio of the two is 7.5:4;

[0052] The preparation method of the modified cyclodextrin core is:

[0053] 2-amino-β-cyclodextrin is mixed with deionized water, stirred to completely dissolve, and a cyclodextrin aqueous solution is obtained, and then sodium polyphosphate is added to the cyclodextrin aqueous solution, and an ice-water bath is used to control the stirring temperature to 3°C, and stirring is performed for 190 minutes. After the stirring is completed, the pH is adjusted to 5.3, and then disuccinimidyl glutarate is added, and the ice-water bath is continued to be used to control the stirring temperature to 3°C, and stirring is performed for 15.5 hours. After the stirring is completed, the product is dialyzed in deionized water and dried to obtain a modified cyclodextrin core;

[0054] The mass ratio of the 2-amino-β-cyclodextrin, deionized water, sodium polyphosphate and disuccinimidyl glutarate is 55:550:1.1:37.

[0055] The preparation method of the shell material is:

[0056] Mix methyl methacrylate-ethyl acrylate copolymer with toluene and stir for 17 minutes. After stirring, add polyaspartic acid ester and continue stirring for 13 minutes. After stirring, add sodium methoxide and control the temperature to 135° C. and stir for 7.5 hours. After stirring, remove toluene by decompression to obtain a shell material.

[0057] The mass ratio of the methyl methacrylate-ethyl acrylate copolymer, toluene, polyaspartic acid ester, and sodium methoxide is 16:80:7.5:1.1;

[0058] In the methyl methacrylate-ethyl acrylate copolymer, the mass ratio of methyl methacrylate monomer to ethyl acrylate monomer is 6.5:4;

[0059] The density of the methyl methacrylate-ethyl acrylate copolymer is 0.918 g / cm 3 ;

[0060] The density of the polyaspartic acid is 1.22 g / cm 3 .

[0061] The preparation method of the high impact modifier is:

[0062] The temperature is controlled at 175°C, the shell material is heated to a molten state, and a shell liquid is obtained for use. The modified cyclodextrin core is then placed in a fluidized bed. Under a nitrogen atmosphere, the modified cyclodextrin core is granulated with the shell liquid. After cooling, the granules, i.e., the high impact modifier, are obtained.

[0063] Comparative Example 1

[0064] Different from Example 1, the step of preparing the modified cyclodextrin core is omitted, and unmodified 2-amino-β-cyclodextrin is used as the core, and the amount is kept unchanged to perform fluidized bed granulation to prepare the impact modifier.

[0065] Comparative Example 2

[0066] Different from Example 1, the step of preparing the polymer shell is omitted, and untreated methyl methacrylate-ethyl acrylate copolymer is used as the shell material, and the amount is kept unchanged to perform fluidized bed granulation to prepare the impact modifier;

[0067] In the methyl methacrylate-ethyl acrylate copolymer, the mass ratio of methyl methacrylate monomer to ethyl acrylate monomer is 6:4.

[0068] Test Example 1 Impact resistance test of impact modifier at room temperature

[0069] According to the method in GB / T1043.1-2008, the samples were prepared. The raw materials in the samples included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of the components in the sample was 1000:50:12:3. Then, according to the method in GB / T1043.1-2008, the impact resistance of the samples of Examples 1-3 and Comparative Examples 1-2 at room temperature (23°C) was tested respectively. The results are shown in Table 1.

[0070] Table 1

[0071]

[0072] In Example 1-3, specially treated cyclodextrin is used as the core of the impact modifier, and then a specially treated methyl methacrylate-ethyl acrylate copolymer is used as the shell to finally prepare the impact modifier. The finally prepared impact modifier can enable polyvinyl chloride to obtain higher impact strength;

[0073] Comparative Example 1 omitted the step of preparing the modified cyclodextrin core and used unmodified 2-amino-β-cyclodextrin as the core. It can be seen that the untreated cyclodextrin core will cause a significant decrease in the impact strength of polyvinyl chloride.

[0074] Comparative Example 2 uses untreated methyl methacrylate-ethyl acrylate copolymer as the shell material. The untreated methyl methacrylate-ethyl acrylate copolymer will cause the impact strength of polyvinyl chloride to decrease to a certain extent.

[0075] Test Example 2 Impact resistance test of impact modifier at low temperature

[0076] According to the method in GB / T1043.1-2008, the samples were prepared. The raw materials in the samples included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of the components in the sample was 1000:50:12:3. Then, according to the method in GB / T1043.1-2008, the impact resistance of the samples of Examples 1-3 and Comparative Examples 1-2 at 0°C, -20°C, and -40°C was tested respectively. The results are shown in Table 2.

[0077] Table 2

[0078]

[0079] In Example 1-3, specially treated cyclodextrin is used as the core of the impact modifier, and then a specially treated methyl methacrylate-ethyl acrylate copolymer is used as the shell to finally prepare the impact modifier. The finally prepared impact modifier can enable polyvinyl chloride to maintain a high impact strength in a low temperature environment;

[0080] Comparative Example 1 omitted the step of preparing the modified cyclodextrin core and used unmodified 2-amino-β-cyclodextrin as the core. It can be seen that the untreated cyclodextrin core will cause a significant decrease in the impact strength of polyvinyl chloride in a low temperature environment;

[0081] Comparative Example 2 uses untreated methyl methacrylate-ethyl acrylate copolymer as the shell material. The untreated methyl methacrylate-ethyl acrylate copolymer will cause a certain degree of decrease in the impact strength of polyvinyl chloride in a low temperature environment.

[0082] Test Example 3 Impact resistance test of impact modifier after sudden heating at low temperature

[0083] According to the method in GB / T1043.1-2008, the samples were prepared. The raw materials in the samples included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of the components in the samples was 1000:50:12:3. Then, according to the method in GB / T1043.1-2008, the samples of test examples 1-3 and comparative examples 1-2 were placed at 0°C, -20°C, and -40°C for 4 hours, respectively. After the placement, they were immediately placed in an oven at a constant temperature of 80°C for sudden heating for 60 minutes. After the sudden heating, the samples were naturally cooled to room temperature, and then the impact resistance of the samples at room temperature (23°C) was tested. The results are shown in Table 3.

[0084] Table 3

[0085]

[0086] In Example 1-3, specially treated cyclodextrin is used as the core of the impact modifier, and then a specially treated methyl methacrylate-ethyl acrylate copolymer is used as the shell to finally prepare the impact modifier. The finally prepared impact modifier can enable polyvinyl chloride to maintain a high impact strength after being suddenly heated in a low temperature environment;

[0087] Comparative Example 1 omitted the step of preparing the modified cyclodextrin core and used the unmodified 2-amino-β-cyclodextrin as the core. It can be seen that the untreated cyclodextrin core will cause the impact strength of polyvinyl chloride to decrease significantly after being suddenly heated in a low temperature environment.

[0088] Comparative Example 2 uses untreated methyl methacrylate-ethyl acrylate copolymer as the shell material. The untreated methyl methacrylate-ethyl acrylate copolymer will cause the impact strength of polyvinyl chloride to decrease to a certain extent after being suddenly heated in a low-temperature environment.

[0089] Test Example 4: Effect of impact modifier on elongation of polyvinyl chloride

[0090] According to the method in GB / T528-2009, the samples were prepared. The raw materials in the samples included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of the components in the samples was 1000:50:12:3. Then, according to the method in GB / T528-2009, the elongation at break of the samples of Examples 1-3 and Comparative Examples 1-2 was tested at room temperature (23°C). In addition, the elongation at break of the samples of Examples 1-3 and Comparative Examples 1-2 was tested at 0°C, -20°C, and -40°C. The results are shown in Table 4.

[0091] Table 4

[0092]

[0093] In Example 1-3, specially treated cyclodextrin is used as the core of the impact modifier, and then a specially treated methyl methacrylate-ethyl acrylate copolymer is used as the shell to finally prepare the impact modifier. The finally prepared impact modifier can make the polyvinyl chloride have a higher elongation at break, and can still maintain a higher elongation at break in a low temperature environment;

[0094] Comparative Example 1 omits the step of preparing the modified cyclodextrin core and uses unmodified 2-amino-β-cyclodextrin as the core. It can be seen that the untreated cyclodextrin core will cause the elongation at break of polyvinyl chloride to be low at room temperature, and the elongation at break in a low temperature environment will decrease to a large extent;

[0095] Comparative Example 2 uses untreated methyl methacrylate-ethyl acrylate copolymer as the shell material. The untreated methyl methacrylate-ethyl acrylate copolymer will cause the elongation at break of polyvinyl chloride to be low at room temperature, and the elongation at break will decrease to a certain extent in a low temperature environment.

[0096] Test Example 5: Effect of impact modifier on transparency and haze of polyvinyl chloride

[0097] According to the method in GB / T2410-2008, the samples were prepared. The raw materials in the samples included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of the components in the sample was 1000:50:12:3. Then, according to the method in GB / T2410-2008, the transparency and haze of the samples of Examples 1-3 and Comparative Examples 1-2 were tested respectively. The results are shown in Table 5.

[0098] Table 5

[0099]

[0100] In Example 1-3, specially treated cyclodextrin is used as the core of the impact modifier, and then a specially treated methyl methacrylate-ethyl acrylate copolymer is used as the shell to finally prepare the impact modifier. The finally prepared impact modifier can make the polyvinyl chloride have higher transparency and lower haze;

[0101] Comparative Example 1 omitted the step of preparing the modified cyclodextrin core and used the unmodified 2-amino-β-cyclodextrin as the core. It can be seen that the untreated cyclodextrin core will cause the transparency of the polyvinyl chloride to decrease to a certain extent and the haze to increase to a certain extent;

[0102] Comparative Example 2 uses untreated methyl methacrylate-ethyl acrylate copolymer as the shell material. The untreated methyl methacrylate-ethyl acrylate copolymer will cause the transparency of polyvinyl chloride to decrease to a large extent and the haze to increase to a large extent.

[0103] Test Example 6 Test on the Effect of Impact Modifier on the Strength of Polyvinyl Chloride

[0104] According to the method in GB / T9341-2008, the samples were prepared. The raw materials in the samples included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of the components in the samples was 1000:50:12:3. Then, according to the method in GB / T9341-2008, the bending strength of the samples of Examples 1-3 and Comparative Examples 1-2 was tested respectively.

[0105] According to the method in GB / T1040.1-2018, the sample was prepared. The raw materials in the sample included polyvinyl chloride, impact modifier, calcium stearate, and polyethylene wax. The mass ratio of each component in the sample was 1000:50:12:3. Then, according to the method in GB / T1040.1-2018, the tensile strength of the samples of Examples 1-3 and Comparative Examples 1-2 was tested respectively;

[0106] The results are shown in Table 6.

[0107] Table 6

[0108]

[0109] In Example 1-3, specially treated cyclodextrin is used as the core of the impact modifier, and then a specially treated methyl methacrylate-ethyl acrylate copolymer is used as the shell to finally prepare the impact modifier. The finally prepared impact modifier can make polyvinyl chloride have higher bending strength and tensile strength;

[0110] Comparative Example 1 omitted the step of preparing the modified cyclodextrin core and used unmodified 2-amino-β-cyclodextrin as the core. It can be seen that the untreated cyclodextrin core will cause a certain degree of decrease in the bending strength of polyvinyl chloride and a greater degree of decrease in the tensile strength;

[0111] Comparative Example 2 uses untreated methyl methacrylate-ethyl acrylate copolymer as the shell material. The untreated methyl methacrylate-ethyl acrylate copolymer will cause a significant decrease in the bending strength of polyvinyl chloride and a certain decrease in the tensile strength.

Claims

1. A polyvinyl chloride high impact modifier, characterized in that: The raw materials of the polyvinyl chloride high impact modifier include a modified cyclodextrin core and a shell material, and the mass ratio of the two is 6.5-7.5:4; The preparation method of the modified cyclodextrin inner core is as follows: 2-amino-β-cyclodextrin is mixed with deionized water, stirred to completely dissolve, and a cyclodextrin aqueous solution is obtained, and then sodium polyphosphate is added to the cyclodextrin aqueous solution, and an ice-water bath is used to control the stirring temperature to 1-3°C, and stirring is performed for 170-190 minutes. After the stirring is completed, the pH is adjusted to 5.1-5.3, and then disuccinimidyl glutarate is added, and the ice-water bath is continued to be used to control the stirring temperature to 1-3°C, and stirring is performed for 14.5-15.5 hours. After the stirring is completed, the product is dialyzed in deionized water and dried to obtain a modified cyclodextrin inner core; The mass ratio of the 2-amino-β-cyclodextrin, deionized water, sodium polyphosphate, and disuccinimidyl glutarate is 45-55:450-550:0.9-1.1:32-37; The preparation method of the shell material comprises the following steps: mixing methyl methacrylate-ethyl acrylate copolymer with toluene, stirring for 13-17 minutes, adding polyaspartic acid ester after the stirring is completed, and continuing to stir for 13-17 minutes, adding sodium methoxide after the stirring is completed, controlling the temperature to 115-135° C., stirring for 7.5-8.5 hours, and removing toluene by decompression after the stirring is completed to obtain the shell material; The mass ratio of the methyl methacrylate-ethyl acrylate copolymer, toluene, polyaspartic acid ester and sodium methoxide is 14-16:70-80:6.5-7.5:0.9-1.1; In the methyl methacrylate-ethyl acrylate copolymer, the mass ratio of methyl methacrylate monomer to ethyl acrylate monomer is 5.5-6.5:4; The preparation method of the high impact modifier is to heat the shell material to a molten state to obtain a shell liquid for use, then place the modified cyclodextrin core in a fluidized bed, and granulate the modified cyclodextrin core with the shell liquid under a nitrogen atmosphere, and after cooling, obtain particles, namely the high impact modifier.

2. A polyvinyl chloride high impact modifier according to claim 1, characterized in that: In the preparation method of the shell material, the density of polyaspartic acid is 1.22 g / cm 3 .

3. A polyvinyl chloride high impact modifier according to claim 1, characterized in that: In the preparation method of the shell material, the density of the methyl methacrylate-ethyl acrylate copolymer is 0.915-0.918 g / cm 3 .

4. The method for preparing a polyvinyl chloride high impact modifier according to claim 1, characterized in that: In the method for preparing the high impact modifier, the shell material is heated to a temperature of 172-178° C. in a molten state.

Citation Information

Cited By

  • Modified impact-resistant ACR for polyvinyl chloride and preparation method of modified impact-resistant ACR

    CN120988211A

  • Modified impact acr for polyvinyl chloride and method for preparing the same

    CN120988211B